h/(-23)=-16

Simple and best practice solution for h/(-23)=-16 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for h/(-23)=-16 equation:



h/(-23)=-16
We move all terms to the left:
h/(-23)-(-16)=0
We add all the numbers together, and all the variables
h/(-23)+16=0
We multiply all the terms by the denominator
h+16*(-23)=0
We add all the numbers together, and all the variables
h-368=0
We move all terms containing h to the left, all other terms to the right
h=368

See similar equations:

| -22=4(y-4)-6y | | -87+6x=83+x | | x/9=-2/7 | | 8/y=2/10 | | -9=-5+r/3 | | m+9÷4=-17 | | 4x^2-13=51 | | 8/y=1/5 | | 2–5x=22 | | w+3(2)=41 | | -7(3b-5)+6=62 | | 6x+40=16x+80 | | z/5+3=-35. | | 3x+3=11x | | -22=4(y+4)-6y | | x+(6/4)=4.6 | | 0.5(8x-4)=6 | | 3-2(x+4)=15 | | .80(20x+12)=-35 | | -73+g×12=-18 | | 2x+38=3,6x-10 | | 2(x)+(6x+12)=180 | | 18=9+x | | -2(+-12)+1=-2n+25 | | 3+2x/5=12 | | x+18=26+x | | 7c=c+48 | | 72/p-(-2)=6 | | 2(x)+(5x+12)=180 | | 16s=672 | | x+15x+5=40 | | –10−10n=–7(3n−8) |

Equations solver categories